Proton Magnetic Resonance Spectroscopy Biomarkers in Neonates With Hypoxic-Ischemic Encephalopathy: A Systematic Review and Meta-Analysis - Zou, Rong; Xiong, Tao; Zhang, Li; Li, Shiping; Zhao, Fengyan; Tong, Yu; Qu, Yi; Mu, Dezhi (Frontiers in Neurology, 2018)
Abstract Background: Hypoxic-ischemic encephalopathy (HIE) is a major contributor to child mortality and morbidity. Reliable prognostication for HIE is of key importance. Proton magnetic resonance spectroscopy (1H-MRS) is a quantitative, non-invasive method that has been demonstrated to be a suitable complementary tool for prediction. The aim of this study was to investigate the prognostic capability of 1H-MRS in the era of therapeutic hypothermia (TH). Methods: Databases, namely MEDLINE, Embase, Web of Science, and the Cochrane library (Cochrane Center Register of Controlled Trials), were searched for studies published before July 17, 2017. Study selection and data extraction were performed by two independent reviewers. The mean difference (MD) or standardized MD (SMD) and 95% confidence interval (CI) were calculated using random-effects models. Subgroup analyses were conducted based on the use of TH. Results: Among the 1150 relevant studies, seven were included for meta-analysis, but only two small studies were conducted under TH. For 1H-MRS measurement, three peak area ratios revealed predictive values for adverse outcomes in TH subgroup and the combined results (with and without TH): N-acetylaspartate (NAA)/creatine in basal ganglia/thalamus (BG/T) in TH (MD -0.31, 95%CI -0.55 to -0.07) and combined results (MD -0.37, 95% CI -0.49 to -0.25); NAA/choline in BG/T in TH (MD -0.89, 95%CI -1.43 to -0.35) and combined results (MD -0.25, 95%CI -0.42 to -0.07); and myo-inositol/choline in cerebral cortex in TH (MD -1.94, 95%CI -3.69 to -0.19) and combined results (MD -1.64, 95%CI -2.64 to -0.64). Moreover, NAA relative concentration is associated with adverse outcomes: in TH (MD -0.04, 95%CI -0.06 to -0.02) and combined results (MD -0.06, 95%CI -0.11 to -0.01) in white matter; in TH (MD -0.04, 95%CI -0.07 to -0.01) and combined results (MD -0.05, 95%CI -0.07 to -0.02) in gray matter. Conclusions: NAA may be a potential marker in outcome prediction for all HIE subjects. It seems that MDs for the ratios of NAA is larger than its relative concentration, and therefore are more likely to be measurable in a clinical context. Larger prospective multicenter studies with a standardized protocol for both measurement protocols and analysis methods are required in future studies.